Motivasi Sebagai Faktor Peningkatan Kinerja Kepolisian di Daerah Provinsi Jawa Barat - Salsadziba Putri Imanda; Kurnia Nurul Azmi; Vanesa Kusuma Dewi; Mic Finanto Ario Bangun (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This study aims to explore whether motivation can enhance the performance of the police force in the West Java Province. The research methodology employed is a literature review, which summarizes and analyzes various previous studies to examine the role of motivation in improving police performance. It is hoped that this research will provide deeper insights into motivation as a factor in enhancing police performance. Previous research findings indicate a positive and significant correlation between motivation and police work discipline, which accounts for 58.3% of their performance. This reaffirms the significant role of motivation in shaping work discipline, which in turn affects the performance of police officers. However, there remain 41.7% of other factors that have not been examined in this study but also influence police performance. The study also demonstrates that high levels of motivation can enhance the performance of police officers, while low motivation can lead to decreased performance. Organizational support has also been proven to play a crucial role in enhancing the work motivation of police officers, ultimately resulting in a positive impact on their performance. It is hoped that the findings of this research will make a significant contribution to the development of human resource management in the Indonesian National Police to improve the performance of its members.